Variation in elemental stoichiometry of the marine diatom Thalassiosira weissflogii (Bacillariophyceae) in response to combined nutrient stress and changes in carbonate chemistry. Issue 4 (10th July 2014) - Clark, Darren R.; Flynn, Kevin J.; Fabian, Heiner; Mock, T.
<x xml:space="preserve">Abstract</x> The combined consequences of the multi‐stressors of pH and nutrient availability upon the growth of a marine diatom were investigated. Thalassiosira weissflogii was grown in N‐ or P‐limited batch culture in sealed systems, with pH commencing at 8.2 ("extant" conditions) or 7.6 ("ocean acidification" [OA] conditions), and then pH was allowed to either drift with growth, or was held fixed. Results indicated that within the pH range tested, the stability of environmental pH rather than its value (i.e., OA vs. extant) fundamentally influenced biomass accumul‐ation and C:N:P stoichiometry. Despite large changes in total alkalinity in the fixed pH systems, final biomass production was consistently greater in these systems than that in drifting pH systems. In drift systems, pH increased to exceed pH 9.5, a level of alkalinity that was inhibitory to growth. No statis‐tically significant differences between pH treatments were measured for N:C, P:C or N:P ratios during nutrient‐replete growth, although the diatom expre‐ssed greater plasticity in P:C and N:P ratios than in N:C during this growth phase. During nutrient‐deplete conditions, the capacity for uncoupled carbon fixa‐tion at fixed pH was considerably greater than that measured in drift pH systems, leading to strong contrasts in C:N:P stoichiometry between these treatments. Whether environmental pH was stable or drifted directly influenced the extent of physiological stress. In contrast, few distinctions could be drawn between "extant" versus "OA" conditions for cell physiology.